Applying Persuasive Communication in Computer-Based Learning: an Analysis Using the Elaboration Likelihood Model - Misroh Pebrianti; Abdul Rasyid; Fakhrur Rozi (Jurnal Spektrum Komunikasi, 2025)
This study aims to get a real picture of persuasive communication in the student learning process at PTPN Computer Laboratory 4 Batu Sondat Village, and also find out the teacher's efforts in achieving student attitudes and character through central and peripheral pathways.This research uses a descriptive approach with qualitative methods. The subjects of the study were teachers and students of PTPN 4 Batu Sondat computer laboratory. Data collection techniques include observation, interviews and documentation. The results showed, using motivational persuasive communication techniques and the theory of Elaboration Likelihood Model with central pathways and peripheral pathways can affect students' understanding of computer science cognitively, affectively, and conatively.